Values that teachers should have from perspectives of principals, teachers, students and parents - Çubukçu, Zühal; Özenbaş, Demet Eker; Çetintaş, Nilüfer; Satı, Derya; Yazlık Şeker, Ümit (Pegem Journal of Education and Instruction, 2012)
Schools as educational institutions bringing children for community are very effective for gaining values. The fundamental goal of schools is to nurture academically successful individuals adopted with basic values. Values are understandings that are sources of behaviors and used to judge them. Schools should work gaining of these basic values through practices by giving place to conscious implementations for gaining of values like tolerance, being fair, sharing, cooperation, being reliable, etc. Activation of values in learning-teaching environment contributes to social and emotional developments of children. For effective learning-teaching environment in gaining values, teachers' consideration of acquisition and accumulation related to values is significant. This study is performed with the purpose of exploring views of principals, teachers, students and parents about the values that teachers should have. Working group of the study includes 5 school principals, 30 teachers, 112 students (9th, 10th, 11th grades) and 50 parents within 2 high schools in the city center of Eskişehir. As a data collection tool, four different question forms are prepared for administrators, teachers, students and parents. Qualitative research method was used. According to analysis esults, 5 themes are reached depending on administrators views. With highest frequency, administrators indicated that teachers should have values as being selfless and tolerate. Teachers expressed their point of views that the most essential value teachers should have is guidance and the least necessary value is use of language. According to students' views, communication ability has the highest frequency as a basic value that teachers should have. Parents give more value to Professional qualifications of teachers. The findings are interpreted in the light of relevant literature.